Conformational Transitions of the Amyloid‐β Peptide Upon Copper(II) Binding and pH Changes. Issue 7 (20th January 2017) - Liao, Qinghua; Owen, Michael C.; Olubiyi, Olujide O.; Barz, Bogdan; Strodel, Birgit
Abstract: Amyloid‐β (Aβ) is a natively unfolded peptide found in all Alzheimer's disease patients as the major component of fibrillar plaques, which are recognized as an important pathological hallmark in Alzheimer's disease. The binding of copper to Aβ increases its neurotoxicity, as Cu 2+ causes Aβ to become redox active and decreases the lag time associated with Aβ aggregation. In addition, the pH is a major factor that influences both the Aβ aggregation rates and Cu 2+ binding. Hamiltonian replica exchange molecular dynamics (H‐REMD) simulations enable atomistic insights into the effects of pH and Cu 2+ complexation on the structure and dynamics of Aβ. To study the Aβ1–42 /Cu 2+ complex, we have developed new force‐field parameters for the divalent copper ion ligated by the two histidine residues, His6 and His13, as well as the amine and carbonyl groups of Asp1, in a distorted square‐planar geometry. Our comparative simulations reveal that both Cu 2+ binding and a low pH‐mimicking acidosis, linked to inflammatory processes in vivo, accelerate the formation of β‐strands in Aβ1–42 and lead to the stabilization of salt bridges, previously shown to promote Aβ aggregation. The results suggest that Cu 2+ binding and mild acidic conditions can shift the conformational equilibrium towards aggregation‐prone conformers for the monomeric Aβ. Abstract :